2012
DOI: 10.1021/es301284h
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Kinetics and Mechanisms at Dolomite–Water Interfaces: Effects of Electrolyte Specific Ionic Strength

Abstract: Elucidating dissolution kinetics and mechanisms at carbonate mineral-water interfaces is essential to many environmental and geochemical processes, including geologic CO(2) sequestration in deep aquifers. In the present work, effects of background electrolytes on dolomite (CaMg(CO(3))(2)) reactivity were investigated by measuring step dissolution rates using in situ hydrothermal atomic force microscopy (HAFM) at 90 °C. Cleaved surfaces of dolomite were exposed to sodium chloride and tetramethylammonium chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Xu et al (2013) used hydrothermal atomic force microscopy to monitor dolomite dissolution in solutions of varying ionic strength. They were able to document increased dissolution rates in more concentrated solutions, although bulk experiments of Pokrovsky et al (2005) found little influence of ionic strength in solutions up to 1 molar.…”
Section: Carbonatesmentioning
confidence: 99%
“…Xu et al (2013) used hydrothermal atomic force microscopy to monitor dolomite dissolution in solutions of varying ionic strength. They were able to document increased dissolution rates in more concentrated solutions, although bulk experiments of Pokrovsky et al (2005) found little influence of ionic strength in solutions up to 1 molar.…”
Section: Carbonatesmentioning
confidence: 99%
“…There have been few studies conducted on dolomite surface reactivity with atomic to nanoscale resolution compared to calcite (Lüttge et al, 2003;Higgins and Hu, 2005;Hu et al, 2005;Fenter et al, 2007;Kazcmarek and Sibley, 2007;Ruiz-Agudo et al, 2011;Urosevic et al, 2012;Xu et al, 2013;Putnis et al, 2014) and, although a significant progress in the understanding of the mechanisms and rates that control dolomite dissolution has been achieved, the complex nature of this mineral still requires detailed investigations to get to a more comprehensive picture of the processes that control its reactivity and formation in natural environments (cf. Kazcmarek and Sibley, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…c, 2 At the mean time, dissolution offers an alternate strategy to understand the mineralization process of biominerals, and to fabricate complex hierarchical ordered materials. For example, the dissolution process of carbonate minerals such as calcite,3 dolomite,4 and magnesite5 has been investigated by many research groups in the last years. Organic molecules with carboxylates and amine groups were supposed to stabilize particular directions and/or planes of calcite through adsorption, coordination complexation, and stereochemical interactions and thus lead to the formation of calcite with different etch pit and hillock shapes through a dissolution process based on investigation results from in situ atomic force microscope (AFM) 3a.…”
Section: Introductionmentioning
confidence: 99%